Motivations and characteristics of patients seeking minimally invasive cosmetic procedures in two Iranian dermatology centers: A cross-sectional study - Sahar Dadkhahfar, MD; Mehdi Gheisari, MD; Yasamin Kalantari, MD; Khatere Zahedi, MD; Amirhooshang Ehsani, MD; Etesami Ifa, MD, MPH (Wolters Kluwer, 2021)
Background: Few studies have evaluated patients' motivations for seeking minimally invasive cosmetic procedures.Objective: This study aimed to assess the demographic characteristics and motivation of patients who seek minimally invasive cosmetic procedures in two academic referral dermatology centers.Methods: The study included adult patients seeking minimally invasive facial cosmetic procedures at two academic dermatology centers in Tehran, Iran, between January 2019 and June 2019.Results: The majority of patients were married, employed women with a mean age of 39.6 ± 10.74 years. The most common region of the face they expected to change was the eyes (56%). Patients who requested fillers desired their cheeks to improve significantly more than patients who requested toxin injections (20.5% vs. 3%; p = .005). Patients had mostly heard about the procedures from friends (40.4%). Approximately one third of patients had experienced a major life event during the preceding year (loss of a family member [50%], marriage [26.9%]). A minority of patients had ever visited a psychiatrist (13.9%), and 15.3% had a history of using psychiatric drugs. The procedure type requested by men was significantly different from that requested by women (88.2% vs. 60.8 % for Botox; 11.8% vs. 34.9% for fillers, and 0% vs. 4.3 % for fat injections; p = .044). The most common motivating factor for patients was gaining rejuvenation (39.2%). The most common preventive factors for patients to undergo the procedures earlier were financial issues (41.7%).Conclusion: Patients seeking minimally invasive cosmetic procedures were married, educated, employed women in their 30s desiring rejuvenation and commonly were not influenced by external factors, such as relationships or the media.